PERANCANGAN SISTEM PEMBELIAN TERHADAP PERUSAHAAN PT SURYA MEGA MUSTIKA - Nugroho, Vidyarto; Stavian Gloryinri Wowor; Charoline Welensia; Angela Halim (Jurnal Serina Abdimas, 2025)
In conducting business activities, companies inevitably deal with both internal and external factors, one of which is the need to have a purchasing cycle. A well-organized purchasing system is crucial for a company to ensure smooth operations and avoid errors in the procurement process. This research aims to design and implement a more efficient purchasing system for PT Surya Mega Mustika. In this Student Creativity Program (PKM), issues were identified based on observations and discussions with the partner company regarding excessive purchasing. Therefore, the company needs to monitor operational transactions to avoid unnecessary cash expenditures. Recurring purchases are an example of an irregularity in the purchasing process. The method used involved presenting materials and conducting online socialization with the partner company. The solution that needs to be implemented by the company is to improve the purchasing system by transitioning from manual processes to a system-based approach. The system is designed to automate the process from requests to purchases, making data management and purchase status monitoring easier. The partner company has recently transitioned from manual to system-based purchasing for a more effective and efficient process. The partner will continue to enhance the system in its operational activities. This PKM was successfully executed according to the established plan. The results of this PKM show that the designed system has made the purchasing process easier, faster, and more organized. The implementation of this system is expected to improve the partner's operational efficiency and provide long-term benefits to the company. ABSTRAK Dalam melakukan kegiatan di dunia bisnis, pastinya tidak lepas dari faktor internal maupun eksternal salah satunya perusahaan harus memiliki siklus pembelian. Sistem pembelian yang baik sangat penting bagi perusahaan untuk memastikan operasional berjalan lancar dan menghindari kesalahan dalam pengadaan barang. Penelitian ini bertujuan untuk merancang dan menerapkan sistem pembelian yang lebih efisien untuk PT Surya Mega Mustika. Pada PKM ini terdapat permasalahan yang diperoleh berdasarkan observasi dan hasil diskusi dengan mitra terkait proses pembelian yang berlebihan, maka perusahaan perlu memperhatikan transaksi yang terjadi dalam kegiatan operasional untuk menghindari pengeluaran kas yang tidak diperlukan. Contoh pembelian berulang merupakan salah satu kejanggalan dalam proses pembelian. Metode yang dilakukan adalah melalui pemaparan materi dan sosialisasi ke perusahaan mitra secara daring. Solusi yang perlu diterapkan perusahaan adalah dengan memperbaiki sistem pembelian yang beralih dari manual ke dalam sistem. Sistem dirancang agar proses permintaan hingga pembelian dapat berjalan otomatis, serta mempermudah pengelolaan data dan pemantauan status pembelian. Mitra baru saja beradaptasi dari manual ke dalam sistem pembelian untuk proses yang lebih efektif dan efisien. Mitra akan terus meningkatkan sistem dalam melakukan kegiatan operasional. PKM ini terlaksana dengan baik dan sesuai rencana yang telah ditetapkan. Hasil dari PKM ini menunjukkan bahwa sistem yang dirancang mampu membuat proses pembelian menjadi lebih mudah, cepat, dan terorganisir. Implementasi sistem ini diharapkan dapat meningkatkan efisiensi operasional mitra dan memberikan manfaat jangka panjang bagi perusahaan